PEMETAAN SERTIFIKASI TANAH WAKAF DI KABUPATEN KAMPAR, PROVINSI RIAU TAHUN 2017 - M. Taufik Hidayatulloh; Selamet Selamet (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
The results showed that, one, the main problem of uncertified wakaf land in Kampar regency is due to technical matters of administration at the time of wakaf registration. Two, among three issues on wakaf processing, the aspect of legal culture is the most common problem. Three, the issue of wakaf management in Kampar regency, Riau Province has not received sufficient attention from local government, religious figures, mass organizations and society in general. Additionally, the Indonesian Wakaf Board (BWI) in Kampar Regency itself has not yet been established to date. Four, the issues found in the office of religious affairs are: (a) the lack of operational funds in the management of wakaf certificates, (b) the lack competence of the administration which still depends on the cross-sectoral institutions, (c) technical weakness of internet network and the weakness of SIWAK system. Five, wakaf land with no AIW while the wakif and witnesses have died in some parts of Kampar Regency have been handled by the head of village. KEY WORDS: Wakaf Land, AIW, Wakaf Management